2005
DOI: 10.1007/s00262-004-0598-5
|View full text |Cite
|
Sign up to set email alerts
|

Thomsen-Friedenreich (TF) antigen as a target for prostate cancer vaccine: clinical trial results with TF cluster (c)-KLH plus QS21 conjugate vaccine in patients with biochemically relapsed prostate cancer

Abstract: The differential overexpression of self-antigens on tumor cells is a prime feature of malignant transformation. Thomsen-Friedenreich (TF), a core disaccharide of O-glycosylated complex glycoproteins, is one of many "self" antigens expressed on malignantly transformed cells that has served as a target for immune recognition and attack. Previously, we conducted clinical trials with a series of synthetic glycolipid, peptide and carbohydrate antigens conjugated to the immunological carrier keyhole limpet hemocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 15 publications
2
68
0
2
Order By: Relevance
“…Synthetic TF and Tn glycoconjugates deserve to be studied from a viewpoint of development of anticancer vaccines [12,13] . Synthetic PAA-glycoconjugates may be promising preparations because they have been described well and can be modified by epitope density or supplemented with the amplifier of immune response and synthesized in necessary quantities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic TF and Tn glycoconjugates deserve to be studied from a viewpoint of development of anticancer vaccines [12,13] . Synthetic PAA-glycoconjugates may be promising preparations because they have been described well and can be modified by epitope density or supplemented with the amplifier of immune response and synthesized in necessary quantities.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic changes of the level of TFand Tn-antibodies in the serum of patients with cancer and its association with survival have been insufficiently studied. Investigations have mainly focused on clinical trials of antigen-specific immunotherapy [12,13] . The authors have undertaken a long-term follow-up of cancer patients to determine changes in the postoperative level of TFand Tn antibodies, as well as to elucidate the association of this level with the progression of cancer, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer vaccines targeting tumor-associated carbohydrates, such as CD176, provide an attractive approach for the prevention and treatment of cancer. Several studies suggested that the vaccination with a CD176 antigen could effectively improve breast cancer patient survival (5,14,15). In patients immunized with CD176 antigen, aside from the activation of CD176-specific antibody responses, a CD176-specific DTH reflecting the activation of specific T cells was also observed (5).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that the CD176 (TF) vaccine was effective and safe for the patients. In the patients immunized with CD176 antigen, CD176-specific delayed type hypersensitivity (DTH; 4,5) and high-titer CD176 IgM and IgG antibodies (15) were observed, indicating that both responses of cellular and humoral immunity are involved in this immunotherapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation